RUSSIA'S INTEREST IN IMPLEMENTING THE 2019 TAX REFORM - Umi, Sentiawati Ibrotul; Tendy, Tendy (Department of International Relations, Universitas Mulawarman, 2026)
The tax maneuver policy implemented by Russia in 2019 was part of fiscal reforms in the energy sector carried out through a gradual reduction in oil export duties and an increase in mineral extraction taxes. These reforms were carried out in response to global oil price fluctuations, international economic pressures, and the Russian government's need to maintain the stability of state revenues. These changes in the tax structure not only affected Russia's domestic economy but also influenced its economic relations with partner countries, particularly Belarus, which had previously benefited from preferential energy pricing mechanisms. This study aims to analyze Russia's interest in implementing the 2019 Tax Maneuver Policy. The method used is qualitative research with a descriptive approach. The results of the study show that the implementation of tax maneuver is not solely aimed at increasing state revenue, but also as a strategy to maintain fiscal stability, strengthen state control over the energy sector, and maintain Russia's economic and political influence in the region, particularly in its relationship with Belarus.